LOCAL LEGISLATIVE DRAFTING IN THE UNITARY STATES: A COMPARISON BETWEEN INDONESIA AND PHILIPPINES - Ekawestri Prajwalita Widiati (Yuridika, 2013)
Local authorities can be found in federal and unitary states. It is the spearhead of the states to enhance a more prosperous and democratic society which provides a range of services in the daily basis. This essay attempts to look at how the national government in unitary states designs local bill-drafting process by doing comparative analysis between Indonesia and Philippines using bill drafting process by Seidmans. By looking at the bill drafting process this essay is trying to figure out the variation of coordination between elements in the local government. Philippines, in this comparative study applied a more radical distribution of power than Indonesia. In Indonesia, however, the relation between the local legislative and executive in the bill-drafting process shows a weak separation. This article conclude that by figuring out the variation of coordination between elements in the local government, at least in Indonesia and Philippines it is seen that coordinated activities in the local legislative process reflects the chosen methods of distributing power taken by the states.Keywords: local authorities, government, local legislative, legislative drafting.